Diagnosis and treatment of Microsporum canis-induced dermatophytosis in a domestic cat - Jainudin , Hizriah Alief; Kemalarani , Mariam (ARSHI Veterinary Letters, 2025)
Dermatophytosis is a common superficial fungal infection in cats, particularly those exposed to outdoor environments. This case study reports a 5-month-old domestic cat named Simon, weighing 1.9 kg, presented with erythematous and scaly skin, partial alopecia, and follicular casts on the head and ear regions. The cat was active, had good appetite, and showed no signs of pruritus. Simon was kept in a semi-outdoor environment with potential contact with stray cats. The diagnosis was based on physical examination, Wood’s lamp test, adhesive tape impression cytology, and fungal culture. Macroscopic and microscopic evaluations of the fungal isolate suggested that Microsporum canis was the causative agent. Treatment included topical antifungal shampoo containing econazole nitrate (Sebazole) applied weekly and systemic itraconazole at a dose of 7.5 mg/kg body weight once daily for two weeks. Supportive therapy included liver (Curcuma FCT) and skin (Coatex) supplements. After two weeks of therapy, physical re-evaluation showed resolution of erythema and scaling, with visible hair regrowth in previously alopecic areas.